Draft genome sequences of three isolates of Coniothyrium glycines, causal agent of red leaf blotch of soybean - Blagden, T.; Espindola, A.; Cardwell, K.; Ortega Beltran, A.; Bandyopadhyay, Ranajit (American Society for Microbiology, 2019)
Coniothyrium glycines, the causal agent of red leaf blotch in soybeans, is considered a high-consequence biological agent. With limited genomic information known, there are no molecular genotyping or detection methods available. We report the draft genome sequences of three C. glycines isolates, greatly enhancing our knowledge of this species.